Metrics in global health: Situated differences in the valuation of human life (2019)
This paper explores the role of knowledge, standards, and metrics in global health. Our point of departure is the observation that the emergence of 'global health' as a domain of research, policy, and practice in the last three decades or so has coincided with an increased interest in the validation and use of measures of health, such as the Disability Adjusted Life Year (DALY), in monitoring and assessing health equity across territories and populations. This 'elective affinity' between global health and health metrics has become the focus of scholarly debate in the social sciences. In this paper, we seek to contextualise and critically discuss the different positions in this debate. We suggest that emplacing health metrics within the neo-liberal logic of health production -one where the 'mechanisms of life' are aligned with the maximisation of economic productivity- does not fully capture the interactive relationship between health measurement and the politics of health. Instead, we argue that this relationship has been characterised by controversy and uncertainty about how to interlock normative ideals and approaches to knowledge-making about health. © 2019 GESIS - Leibniz Institute for the Social Sciences. All rights reserved.